2003
DOI: 10.1046/j.1460-9568.2003.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphine withdrawal‐induced abnormalities in the VTA: confocal laser scanning microscopy

Abstract: Morphine withdrawal is characterized by functional alterations at the level of the ventrotegmental area. We investigated the effects of chronic morphine administration and withdrawal on the morphological properties of immuno-labelled tyrosine hydroxylase-positive neurons of the rat ventrotegmental area with a confocal laser scanning microscope. Morphological evaluation revealed a reduction in the area and perimeter of tyrosine hydroxylase-positive somata in morphine-withdrawn rats. Conversely, the number of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 42 publications
9
50
1
Order By: Relevance
“…This increased rate then normalizes, or even decreases below baseline, in animals withdrawn from the opiate. Because there is evidence from our own work (Russo et al 2007), and others (Spiga et al 2003), that the soma size is also decreased at these later time-points, when firing rate has decreased, it may be the initial sustained increase in firing rate that is vital for induction or maintenance of the morphological change. In contrast, LC neuronal activity is acutely decreased by morphine administration, returns toward baseline levels in vivo with chronic administration, and only increases above normal levels on opiate withdrawal.…”
Section: Opiate-induced Structural Plasticitymentioning
confidence: 71%
See 1 more Smart Citation
“…This increased rate then normalizes, or even decreases below baseline, in animals withdrawn from the opiate. Because there is evidence from our own work (Russo et al 2007), and others (Spiga et al 2003), that the soma size is also decreased at these later time-points, when firing rate has decreased, it may be the initial sustained increase in firing rate that is vital for induction or maintenance of the morphological change. In contrast, LC neuronal activity is acutely decreased by morphine administration, returns toward baseline levels in vivo with chronic administration, and only increases above normal levels on opiate withdrawal.…”
Section: Opiate-induced Structural Plasticitymentioning
confidence: 71%
“…Additionally, this change could be blocked by systemic naltrexone, suggesting that MOR signaling was required, and local brain-derived neurotrophic factor (BDNF) infusion in VTA also prevented the decrease, suggesting that decreased neurotrophic signaling may underlie the morphological change. Importantly, this reduction in VTA DA neuron soma size is observed with chronic administration of heroin as well as morphine (Russo et al 2007), in passive and self-administration protocols (Spiga et al 2003;Chu et al 2007;Russo et al 2007), and across species, as we have recently characterized this effect in mouse and in postmortem tissue from human heroin abusers (Mazei-Robison et al 2011). Follow-up studies found no evidence of VTA DA neuronal death or injury (Sklair-Tavron et al 1996;Russo et al 2007) and that the decrease in cell size persists for 14 days after chronic morphine administration, but returns to baseline by 30 days.…”
Section: Opiate-induced Structural and Cellular Plasticitymentioning
confidence: 89%
“…When the VTA, NAc and central or lateral nucleus of amygdala were lesioned with a DC current, morphine-induced conditioned place preference (CPP) can be inhibited . Morphological study showed that the both volume and number of neurons in the VTA and NAc in morphine withdrawal rats decreased (Spiga et al, 2003). There are also evidence that indicates drug-seeking in morphine-dependent rats and heroin-induced self-administration are related to the electrical activities of DA neurons in the VTA and NAc (Chang et al, 1997;Kiyatkin and Rebee, 2001).…”
Section: Anatomy Of Mesocorticolimbic Dopaminergic Regionsmentioning
confidence: 99%
“…Natural reward behaviors are mediated by the mesocorticolimbic system (Meisel and Mullins, 2006;Hoebel et al, 2009;Pitchers et al, 2010a;Young et al, 2011;Blum et al, 2012). Drugs of abuse cause neural alterations in this system, which in-turn contribute to development and expression of substance abuse (Hyman et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs of abuse cause neural alterations in this system, which in-turn contribute to development and expression of substance abuse (Hyman et al, 2006;. We previously determined that experience with natural reward behavior, i.e., sexual experience in male rats, also causes neural plasticity in the nucleus accumbens (NAc), including increased dendritic spines and deltaFosB (Pitchers et al, 2013). Inturn, this sex-induced plasticity is critical for the effects of sex experience on subsequent mating, manifested as the facilitation of initiation and performance of sexual behavior (Pitchers et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%